Physicochemical Characteristics and Functional Properties of White Sweet Potato Starch - Widya Rahmawaty Saman; Indah Yuliasih; Sugiarto (International Journal of Engineering and Management Research, 2019)
Sweet potato is an agricultural commodity that is a source of high carbohydrates and can be cultivated in infertile areas. Processing of sweet potatoes as food and industrial raw materials is still limited. One way to process sweet potatoes is to dry the sweet potato into starch so that it can increase the sweet potato storage capacity as well as being beneficial and practical in storage and transportation so that it can be processed into various food products. The purpose of this study was to study and evaluate the physicochemical characteristics and functional properties of white sweet potato starch varieties of AC. Various methods are used to analyze these characteristics and properties, including the kjedahl method, AOAC (Association of Official Analytical Chemistry), SNI (Indonesian national standard) and several methods that have been developed. The results showed that the values ​​of 9.02% moisture content, 0.37% ash content, 0.62% crude fiber, 0.13% fat content, 85.23% starch content, 35.99% amylose content, 88.75% carbohydrate content, 77.14% white degree freeze-thaw stability 95.18 % and clarity of starch paste 44.97%. Characteristics obtained have met the standards, but each variety has advantages and disadvantages so that it can be adjusted to the use of food products that want to use AC sweet potato varieties of white sweet potato.